DIAGNOSIS AND CLASSIFICATION OF THYROID DISEASES - Shonazarova Nodira Xudoyberdiyevna; Toshtemirov Bobomurod Behzodjon o’g’li (Research Focus International Scientific Journal, 2025)
Thyroid hormones affect the entire metabolism in the body and participate in the growth and formation of all organs and tissues. Due to the increase in thyroid diseases, we focused on the prevalence and classification of this pathology.